2011
DOI: 10.1021/jo2003715
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free or Low-Solvent Large-Scale Preparation of Chloropyrimidine and Analogues

Abstract: Chloropyrimidine or other N-containing aromatic heterocyclic analogues can be efficiently prepared from the corresponding hydroxylated precursors under solvent-free or low-solvent conditions with equimolar or less chlorinating reagents. This high-yielding protocol allows successful preparations of multigram and kilogram batches of these important synthetic intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Yet, the isolated yield was very good at 88% for the dichloro product, indicating that each POCl 3 provided more than one chlorine atom to form the final product. This result is consistent with findings in our original report that in some cases even substoichiometric amount of POCl 3 was sufficient to produce respectable results using our solvent-free protocol [ 7 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Yet, the isolated yield was very good at 88% for the dichloro product, indicating that each POCl 3 provided more than one chlorine atom to form the final product. This result is consistent with findings in our original report that in some cases even substoichiometric amount of POCl 3 was sufficient to produce respectable results using our solvent-free protocol [ 7 ].…”
Section: Resultssupporting
confidence: 93%
“…We recently reported a protocol for large scale (milligram to kilogram batches) chlorination of hydroxypyrimidines using equimolar or less POCl 3 with heating in a sealed reactor under solvent-free or low solvent conditions [ 7 ]. Our procedure has simple work up steps involving filtration or distillation, and generally gives high yields and purity of final products.…”
Section: Introductionmentioning
confidence: 99%
“…This would circumvent the Balz–Schiemann chemistry, avoiding associated safety/handling challenges and the product loss due to 8 . 2,6-Dichloropurine 11 is readily available in two well-established steps from guanine, and precedent in the literature showed that the halogen exchange could likely be induced by benign fluoride salts. ,, …”
Section: Resultsmentioning
confidence: 99%
“…A variety of conditions and combinations of catalyst systems, bases, and solvents were screened for optimal reaction conditions for 2,4‐dichloroquinazoline (derived from anthranillic acids and urea followed by chlorination with POCl 3 ) with phenyl boronic acid (Table ). Interestingly, under most of the reaction conditions, C4 hydroxylated/C2 arylated was the major product, with varying amounts of C2 and C4 diarylation product resulting from different aryl/heteroaryl boronic acid.…”
Section: Resultsmentioning
confidence: 99%